Comparing the pertussis antibody levels of healthy children immunized with four doses of DTap-IPV/Hib (Pentaxim) combination vaccine and DTaP vaccine in Quzhou, China - Yin, Zhiying; Zheng, Canjie; Fang, Quanjun; Wen, Tingcui; Wang, Shuangqing; Li, Junji; Gong, Xiaoying; Xiang, Ziling (Frontiers in Immunology, 2023)
Despite the high coverage of pertussis vaccines in high-income countries, pertussis resurgence has been reported in recent years, and has stimulated interest in the effects of vaccines and vaccination strategies. Immunoglobulin G (IgG) antibodies against pertussis toxoid (PT), filamentous hemagglutinin (FHA), and pertactin (PRN) after immunization with four doses of co-purified or component vaccines were determined by enzyme-linked immunosorbent assay (ELISA). Serological data of PT-IgG geometric mean concentrations (GMCs) over time since vaccination were used to fit the mathematical models. A total of 953 children were included in this study; 590 participants received four doses of the component acellular vaccine and 363 participants received four doses of the co-purified acellular vaccine. The GMCs and the seropositivity rate of pertussis IgG were significantly influenced by the production methods, and the immunogenicity of the component acellular vaccine was superior to that of the co-purified acellular vaccine. The fitted mathematical models for the component acellular vaccine and the co-purified acellular vaccine were Y=91.20e-0.039x and Y=37.71x-0.493, respectively. The initial GMCs of the component acellular vaccine was higher than that of the co-purified acellular vaccine, but both were similar at 72 months after immunization. Pertussis IgG levels waned over a longer time after four doses of acellular pertussis vaccine, regardless of whether component or co-purified vaccine was used. The development and promotion of new vaccines should be accelerated in China, and booster doses of pertussis vaccine in adolescents, adults, and pregnant women should be employed.